Infrastructure Finance in Armenia - World Bank Group (World Bank, Washington, DC, 2018)
In order to sustain economic growth, Armenia needs to invest in infrastructure – much of this on a commercial basis given the limited fiscal space available and high level of public debt. The private sector has actively participated in infrastructure investment in Armenia, notably by way of divestiture, concessions, lease, and management contracts. Beyond direct state funding from current tax revenues, infrastructure investment can be commercially financed through a mix of (a) public finance (borrowing guaranteed by the state), (b) corporate finance (loans to corporate borrowers), (c) project finance (loans to project companies repaid from future cash flows).This entails, successively: (i) identifying whether parts of an infrastructure development program can be financed on commercial terms; (ii) when commercial financing is not viable, undertake upstream reforms to strengthen policies, regulations, institutions and capacity; (iii) if reforms are not sufficient, explore the possibility of deploying concessional and public resources to strengthen the bankability of priority investments; and finally (iv) where commercial financing is not feasible despite sector reform and risk mitigation, mobilize public and concessional resources. Armenia’s infrastructure finance agenda touches upon three key dimensions: (a) the origination of an abundant, mature pipeline of bankable infrastructure projects, (b) a business climateconducive to commercial investment in infrastructure, and (c) the availability of long-term financing for infrastructure projects. The country needs to systematize its pipeline of infrastructure projects and strengthen the origination of transactions. The existing regulatory framework needs to incorporate specific provisions for PPPs, and practices need to be improved. Going forward, financing from multilateral and bilateral sources will need to be complemented by other sources, notably international and domestic commercial banks. Local banks have increased long-term lending in recent years, but still only have limited involvement in infrastructure finance. Internationally, states have attempted various types of interventions in support of infrastructure finance. First, the state may support priority projects that are economically viable, but whose financial returns are not high enough, or are sufficiently predictable, to attract the interest of private sector investors. Such schemes, involving financial viability support (FVS), are generally incorporated in the host country’s PPP framework, and can take different forms, such viability gap funds (VGF) and availability payment (AP) schemes. Given the size of the economy, and the dearth of bankable projects, priority should be given to assessing the feasibility of financial viability support, and possibly wholesale financial sectorinterventions, rather than retail interventions.